.45-caliber widow maker [large type] - Brandvold, Peter (Wheeler Publishing large print Western, 2009)
Cuno Massey is determined to start a new, peaceful life. But when he comes across a prison wagon under attack, he can't just ride on. A gang of outlaws is hell-bent on granting four hardened convicts an early release, and with the only lawman down, the marshal is badly outnumbered. Dispensing frontier justice from the barrel of his Colt .45, Cuno does his best to even the odds and keep the murderous animals where they belong.